2017
DOI: 10.1007/s12185-017-2245-x
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic hematopoietic stem cell transplantation for refractory mycosis fungoides (MF) and Sezary syndrome (SS)

Abstract: Cutaneous T cell lymphoma is a heterogeneous group of lymphoproliferative disorders with different clinical behavior and prognosis in which malignant T cells accumulate in the skin. In the relapsed/refractory stage, treatment strategy varies depending on clinical perspective. We retrospectively evaluated advanced stage relapse or refractory mycosis fungoides and Sezary syndrome patients who underwent allogeneic hematopoietic stem cell transplantation (allo-HSCT) at our hospital. The overall response rate was 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…Refractory MF and capability of progression to systemic MF may be related with innate or adaptive immune system during disease course. In fact, allogeneic hematopoietic stem cell transplantation [ 20 ] or immune check point inhibitor [ 21 ] is considered as effective treatment for refractory or relapsed MF. In particular, a patient with refractory cutaneous T-cell lymphoma had a chimeric cytotoxic T lymphocyte antigen (CTLA4)-CD28 fusion, and the blockade of this chimeric fusion using ipilimumab showed marked response without toxicities [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Refractory MF and capability of progression to systemic MF may be related with innate or adaptive immune system during disease course. In fact, allogeneic hematopoietic stem cell transplantation [ 20 ] or immune check point inhibitor [ 21 ] is considered as effective treatment for refractory or relapsed MF. In particular, a patient with refractory cutaneous T-cell lymphoma had a chimeric cytotoxic T lymphocyte antigen (CTLA4)-CD28 fusion, and the blockade of this chimeric fusion using ipilimumab showed marked response without toxicities [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The malignant T cells show constitutive activation and propensity for T-helper 2 cytokine production [ 8 ] that suppresses cell-mediated immunity and increases infection risk [ 1 ]. Unfortunately, CTCL remains generally incurable except in rare cases of allogeneic stem cell transplantation [ 9 ]. Overall response rates to single agent systemic therapies, including the retinoid bexarotene, and histone deacetylase (HDAC) inhibitors vorinostat and romidepsin, range between 20–45% and relapses are not uncommon [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Allogeneic hematopoietic stem cell transplantation may be a promising treatment for advanced MF and SS. 3 , 4 However, there is no established consensus on management after transplantation. A previous report showed that the rate of progression or relapse 1 year after transplantation was 50% and found that relapse is most common in the first year post-transplantation.…”
Section: Introductionmentioning
confidence: 99%